Escherichia coli infections - Manning, Shannon D., 1971-; Babcock, Hilary (New York : Chelsea House, 2010)
Examines escherichia coli by looking at up-to-date information on the different strains of E. coli, including the latest outbreaks, statistics, diagnostic breakthroughs, and vaccine development.
Outbreaks -- What is E. coli? -- E. coli diseases -- E. coli colonization and transmission -- Epidemiology of E. coli infections -- Disease pathogenesis -- Diagnosis and treatment -- Disease prevention -- Future possibilities and concerns.
Includes bibliographical references (p. 117-124) and index.
Keywords: Escherichia coli infections; Escherichia coli; Escherichia coli Infections; Escherichia coli; Escherichia coli; Escherichia coli infections